Lymph node core biopsies reliably permit diagnosis of lymphoproliferative diseases. Real‐World Experience from 554 sequential core biopsies from a single centre. (2nd December 2020) - Cohen, Oliver C.; Brodermann, Maximillian H.; Dervin, Aoife; Raja, Neel; Marafioti, Teresa; Otero, Sofia; Beale, Tim; Jawad, Susan; Ramsay, Alan; Pomplun, Sabine; Ardeshna, Kirit M.; Proctor, Ian; et al.
Abstract: Introduction: Whilst excision biopsy is traditionally preferred, advances in radiological and histological techniques warrant a re‐look at core biopsy as a viable primary diagnostic method. Method: Over a 3‐year period, all patients who underwent core biopsy to investigate lymphoma at our centre were included. Results: 554 consecutive patients were included (40.1% prior lymphoma and 59.4% new presentations). Three or more cores were taken in 420 (75.8%) cases. Median time from request to biopsy and biopsy to histology report was 2 (0‐40) days and 7 (1‐24) days, respectively. 510/544 (93.8%) biopsies were diagnostic. There was no difference in whether the biopsy was diagnostic based on indication (new vs. relapsed lymphoma) ( P  = .445), whether biopsy was PET‐directed ( P  = .507), for T‐cell lymphoma ( P  = .468) or nodal vs. extra‐nodal ( P  = .693). Thirty‐eight patients (6.9%) required a second biopsy due to inadequate tissue. In a patient experience survey, only 13.9% reported any complications (1 self‐limiting minor bleeding, 4 bruising) whilst 16.7% reported any discomfort beyond 12 hours. Conclusion: Core biopsy performed by experienced radiologists and analysed by expert haemato‐pathologists is a reliable, well‐tolerated method for diagnosing lymphoma and confirming relapse. Multiple cores can be obtained under local anaesthetic yielding sufficient material in the majority of cases.